Prevention of cardiovascular disease in patients recovering from use of psychoactive substances - Silvânia Maria Mendes Vasconcelos; Francisca Lígia de Medeiros Martins dos Santos; Thereza Maria Magalhães Moreira; Maria Tereza Viana Lima; Rita Neuma Dantas Cavalcante de Abreu; Adelaide Amorim Cavalcante Abreu; Gilson Holanda Almeida (Universidade de Fortaleza, 2012)
Objective: Assess the knowledge of people recovering from substance abuse, after performance of educational activities, about the risk factors of cardiovascular diseases. Methods: This was a quantitative study involving 36 patients receiving treatment in the detoxification unit of a public psychiatry hospital in the State of Ceará, Brazil. All subjects were consenting adults over the age of 18 years. A questionnaire was used before and after an educational activity that measured the level of knowledge and understanding of cardiovascular disease and related risk factors. Results: The results demonstrated that initially, 19 (52.8%) people confirmed that they were not aware of any cardiovascular disease but after the activity, this number dropped to 4 (11%). In addition, the reference to the risk factors for diseases of the circulatory system was evaluated, when it became evident that, before the educational activity, 22 (61%) did not know these factors, another 14 (39%) cited one or two, especially a diet rich in fat and the use of illegal drugs. After the activity only 3(8%) did not know and the other 33 (92%) were able to cite the use of legal drugs, obesity, and a sedentary lifestyle. Conclusion: Educational intervention resulted in a significant change in participants´ knowledge of cardiovascular risk factors, which may help result in improvement in the lifestyle of patients, as well as their families.